2005
DOI: 10.1097/00129492-200501000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Hearing and Sound Localization with and without an Air Interface

Abstract: The presence of air around the pinna and inside the external ear canal did not improve underwater hearing sensitivity or sound localization. These results support the argument that bone conduction plays the main role in underwater hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Actually we do not agree, our results clearly argue for the sound transmission via the middle ear. Neoprene hoods worsen underwater sound perception, which is known from the literature [7,10] and could be supported by our findings. However, we could not support the measurements reported by Hollien and Feinstein [5], according to which it makes no difference whether there is a perforation in the neoprene hood above the ear or not: our recordings showed at least a small effect.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Actually we do not agree, our results clearly argue for the sound transmission via the middle ear. Neoprene hoods worsen underwater sound perception, which is known from the literature [7,10] and could be supported by our findings. However, we could not support the measurements reported by Hollien and Feinstein [5], according to which it makes no difference whether there is a perforation in the neoprene hood above the ear or not: our recordings showed at least a small effect.…”
Section: Discussionsupporting
confidence: 92%
“…This in agreement with the findings of Bauer and co-workers [1,3] and in contradiction to the assumption by Hollien et al [4,5]. Other authors favor a third theory, according to which as a dual path theory both mechanismsbone conduction and middle ear conductionplay a role, contributing differently to underwater sound perception depending on different frequencies [7,8]. One of the main difficulties in underwater hearing is that the acoustic impedance of water is much higher than that of air.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…22 Recently, Shupak et al tested the use of masks with an air pocket around the ears as a method of improving underwater auditory perception; however, the authors concluded that the masks did not significantly improve underwater hearing. 23 Among scuba divers, poor sound localisation is a source of concern as certain sounds may indicate imminent danger, such as an approaching motorboat. In the current study, the results of the spatial localisation tasks among the sighted controls indicated that they could only immediately identify the source of sound at a rate of 24%; therefore, the task was feasible in only one out of four attempts.…”
Section: Discussionmentioning
confidence: 99%